How Can We Live in the Common World? Truth, Being-With and the World in the Early Heidegger - Seol, Min (Acta Philosophica, 2020)
According to the early Heidegger, the world is disclosed in dependence on Dasein, which is a term for each of us. A question arises as to how the world can be established despite the particular existence of Dasein. After reviewing previous discussions of the question, I elucidate the priority of the world over my world based on Heidegger’s lecture in 1928/29, which contains a considerable discussion of the relationship between Being-with (Mitsein) and truth. According to him, since truth is essentially communal and cannot be privatized, the sphere of truth manifested by a particular Dasein is open to all other Dasein. This openness signifies, I argue, the ontological priority of an open realm that covers every sphere of truth. This open realm is no different from the world that is ontologically disclosed in common. Based on this common world-disclosure, each Dasein discloses its own world according to its life history.